Clinical Value of Measurement of Internal Auditory Canal in Pediatric Cochlear Implantation. (June 2019) - Kim, Hantai; Kim, Dong Young; Ha, Eun Ju; Park, Hun Yi
Objectives: The aims of this study were to clarify the clinical value of the bony cochlear nerve canal (BCNC) and internal auditory canal (IAC) in children with bilateral sensorineural hearing loss (b-SNHL) and to reveal the correlation between these parameters and outcomes after cochlear implantation (CI). Methods: Ninety-four ears with b-SNHL that received CI and 100 ears with normal hearing were enrolled. Parameters of IAC and pre- and post-CI categories of auditory performance scores were analyzed. Results: The width of the BCNC and the width, height, and length of the IAC were shorter in the b-SNHL group. BCNC and IAC width were associated with b-SNHL. The calculated cutoff values for BCNC and IAC width were 2.055 mm in the BCNC and 4.245 mm in the IAC, setting the sensitivity to 90%. Patients with narrow BCNCs and IACs had significantly worse post-CI auditory performance. Conclusions: BCNC and IAC widths were narrower in children with b-SNHL than in normal-hearing children. Narrow BCNC and IAC width had a negative impact on post-CI outcomes. The proposed cutoff values for BCNC and IAC width were meaningful when predicting the auditory outcome after CI, especially considering both.